How much should we trust linear instrumental variables estimators? An application to family size and children's education - Magne Mogstad; Matthew Wiswall (Institute for the Study of Labor (IZA), 2009)
Many empirical studies specify outcomes as a linear function of endogenous regressors when conducting instrumental variable (IV) estimation. We show that tests for treatment effects, selection bias, and treatment effect heterogeneity are biased if the true relationship is non-linear. These results motivate a re-examination of recent evidence suggesting no causal effect of family size on children's education. Following common practice, a linear IV estimator has been used, assuming constant marginal effects of additional children across family sizes. We find that the conclusion of no effect of family size is an artifact of the linear specification, which masks substantial marginal family size effects.
Keywords: C31; C14; J13; 330; Instrumental variables; variable treatment intensity; treatment effect heterogeneity; selection bias; quantity-quality; family size; child outcome; Instrumentalvariablen-Schätzmethode; Kausalanalyse; Schätztheorie; Kritik; Schätzung; Familie; Kinder; Bildungsniveau; Norwegen